Epidemiological and mechanistic links between PM2.5 exposure and type 2 diabetes: focus on the TRPV1 receptor - Liviero, Filippo; Pavanello, Sofia (Frontiers in Endocrinology, 2025)
The growing global burden of type 2 diabetes (T2D) has prompted increasing attention to environmental factors that may contribute to its development. Among these, exposure to fine particulate matter (PM2.5) has emerged as a significant yet often overlooked risk factor. This systematic review conducted according to the PRISMA guidelines, provides a comprehensive and critical appraisal of the epidemiological evidence and discusses mechanisms linking PM2.5 exposure to the onset and progression of T2D. Long-term exposure to PM2.5 has been consistently associated with increased T2D risk in epidemiological studies, particularly among vulnerable groups such as individuals with obesity, metabolic syndrome, or advanced age. In addition, evidence from animal models suggests that acute exposure can exacerbate insulin resistance and impair glucose metabolism. Mechanistic studies highlight the roles of oxidative stress, systemic inflammation, endothelial dysfunction, and autonomic imbalance. Notably, recent findings implicate the transient receptor potential vanilloid 1 (TRPV1) in neurogenic inflammation and metabolic disruption, offering novel insights into how PM2.5 may influence glycemic control. Experimental evidence in humans indicates that traffic-related PM2.5, including diesel exhaust particles (DEPs), activates TRPV1, supporting its role as a molecular interface between environmental insults and metabolic disruption. Given its central role in neurogenic inflammation and metabolic regulation, TRPV1 has emerged as a promising therapeutic target. Preclinical studies have shown that pharmacological modulation of TRPV1 improves glucose tolerance and reduces inflammation. Currently, XEN-D0501, a TRPV1 antagonist, is undergoing clinical trials to assess its efficacy in regulating blood glucose and mitigating T2D-related inflammatory complications. These mechanistic insights are further supported by animal studies demonstrating that PM2.5 exposure induces metabolic dysfunction consistent with TRPV1 activation and inflammation-related pathways. Animal models corroborate human data, revealing that PM2.5 exposure promotes visceral adiposity, impairs hepatic insulin signaling, and triggers tissue-specific inflammation. Despite the strength of the overall evidence, heterogeneity in exposure assessment, driven by spatial and temporal variations in PM2.5 sources and composition, and in study design persists. Given the ubiquity of PM2.5 in urban environments, even modest increases in diabetes risk may translate into substantial public health burdens. Targeted policies to reduce air pollution, together with intensified research into biological susceptibility and prevention strategies, are essential. Addressing PM2.5 as a modifiable determinant of T2D represents a timely and actionable priority in environmental health.